Cell Metabolic Diagnosis and Control in CHO Fed-batch Process. Issue 7 (2022) - Kuang, Bingyu; Hoang, Duc; Wang, Zhao; Yoon, Seongkyu
Abstract: Therapeutic protein productivity and product quality highly rely on cell metabolism of the fed-batch process, which is a costly, time-consuming and lack of intracellular analytical diagnostic tools. Cell culture medium composition and feeding strategy is critical to regulate cell metabolism. In this study, we present an unorthodox approach to optimize CHO bioprocess by integrating conventional design-of-experiments (DOE) methodology with genome scale model (GEM) flux analysis. Generic CHO-K1 metabolic model was tailored and further integrated with CHO fed-batch metabolomic data to obtain a cell line- and process-specific model. In silico metabolic flux analysis was conducted via GEM to identify the critical medium components toward cellular growth and further evaluate their optimized flux values from thirty five simulated fed-batch DOE conditions. Glucose and valine were projected as the most critical nutrients in the process from the flux simulation analysis. Using this approach, previously identified metabolic inhibitor cytidine monophosphate accumulated in extracellular environment was found to be regulated by glucose, glutamine, aspartate, and alanine and further experimentally validated through dose-dependent amino acid spiking study. A process diagnostic and control model was constructed from network topology modeling constructed through GEM and pathway enrichment analysis, which allowed optimization of medium components utilized in a fed-batch feeding process to better support cell metabolism and mitigate accumulation of metabolic inhibitors.